1990
DOI: 10.1029/jd095id09p13897
|View full text |Cite
|
Sign up to set email alerts
|

Particle size distribution and chemistry of late winter Arctic aerosols

Abstract: Mass size distributions of element concentrations in Arctic aerosols at Barrow, Alaska, were measured from March 16 to May 6, 1986, and their correlations were examined statistically by absolute principal component analysis. In eight particle size fractions from <0.25 to >16 }xm aerodynamic diameter (gmad), from eight-stage cascade impactor sampling and proton-induced X-ray emission (PIXE) analysis, four types of aerosol components were resolved. One, resembling sea salt in composition, shows a maximum mass at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Only a minor fraction of the mass of Fe, Ca, and K is located in the submicrometer size range for the background sample W11. This is in agreement with general observations worldwide [Milford and Davidson, 1985], studies in the low Arctic [Li and Winchester, 1990], and previous studies on the Greenland Ice Sheet [Hillarno et al, 1993]. As pointed out previously, these species are mostly from crustal origin and thus located in the coarse mode.…”
Section: Aerosol Size Distributions: Submicron Modessupporting
confidence: 93%
See 1 more Smart Citation
“…Only a minor fraction of the mass of Fe, Ca, and K is located in the submicrometer size range for the background sample W11. This is in agreement with general observations worldwide [Milford and Davidson, 1985], studies in the low Arctic [Li and Winchester, 1990], and previous studies on the Greenland Ice Sheet [Hillarno et al, 1993]. As pointed out previously, these species are mostly from crustal origin and thus located in the coarse mode.…”
Section: Aerosol Size Distributions: Submicron Modessupporting
confidence: 93%
“…It is noteworthy that the peak in coarse mode sulfur is closer to the maximum in the surface area distribution of the crustal species. Similar switches in the size distributions of sulfur have been presented for the Arctic aerosol at sea level by Li and Winchester [1990]. This result is expected if sulfate is primarily formed through heterogeneous reaction of SO2 at the particle surface [Kerninen et al, 1998], as opposed to a primary origin in soil particles as calcium sulfate in the coarse fraction [Legrand, 1995].…”
Section: Meteorology Figure 3 Presents the Isentropic Air Mass Back supporting
confidence: 70%
“…Fine-fraction aerosols are commonly accepted to be good indicators of long-range transport [Li and Winchester, 1990;Thurston and Spengler, 1985;Junge, 1979]. In general, coarse aerosols tend to have local origins [Gatebe, 1999;Li and Winchester, 1990;Maenhaut et al, 1996]. An exception is coarse-fraction C1, which has been shown to be a clear indicator of transport from ocean areas .…”
Section: Long-range Transport Of Trace Elements To Mount Kenyamentioning
confidence: 99%
“…Since previous work by Li and Winchester [1990] had shown that marine biogenic sulfur was a significant fraction of the fine-mode aerosol mass at Barrow in late April 1986, we carried out a third set of field measurements over the Arctic Ocean in April 1992. Table 3 Unfortunately, two of the gold tubes for the "final experiment" samples were damaged and produced no usable results.…”
Section: April 1992 Airborne Measurementsmentioning
confidence: 99%